Biology, A to Z Handbook (fourth edition) - Indge, Bill (VIVA BOOKS PRIVATE LIMITED; India, 2014)
A powerful aid to improve your grade The Biology: A to Z Handbook explains all the key terms and has been completely updated. Each entry begins with a clear definition and is followed by explanation worked examples and cross-references where relevant. The handbook provides expert advice from a leading author that will help familiarise you with the language of biology - the more important the term the more detailed the entry. It is invaluable for students teachers as well as general readers. For new students - terms and concepts clearly explained Throughout the course - full explanations of important and challenging concepts that will help you tackle your course assignments with confidence